Chinese Exchange Rate Policy: Lessons for Global Investors. Issue 1 (5th May 2021) - Melvin, Michael; Westermann, Frank
Abstract: In 2015, the People's Bank of China announced a new exchange rate policy where the RMB central parity rate is determined each morning by the previous day's closing rate, market demand and supply, and valuations of other currencies. This policy suggests an implementable investment strategy for trading the CNH. We create a forecasting model that can be used to manage the global investor's problem of mitigating the currency risk inherent in Chinese equity positions. A dynamic currency overlay strategy, where the forecasting model is used as a trading signal to take long and short positions in CNH, performs particularly well.